Baselining Activity and Stability of ORR Catalysts and Electrodes for Proton Exchange Membrane Fuel Cells for Heavy-Duty Applications. Issue 2 (1st February 2023) - Wang, X.; Hu, L.; Neyerlin, K. C.; Ahluwalia, R. K.
Abstract : Activity and stability of electrodes with Pt and PtCo alloy catalysts supported on high surface area carbon, hereafter to as a-Pt/C and d-PtCo/C, were evaluated for heavy-duty applications. Both catalysts had nearly identical Pt loading (50-wt% Pt on carbon and 0.25 mgPt cm −2 ) and had undergone thermal treatment to stabilize them by growing the average particle size to 4–5 nm. Both were subjected to 90, 000 (90 k) standard accelerated stress tests (AST) cycles consisting of 0.6–0.95 V square wave potentials, 3-s hold at upper and lower potential limits in H2 /N2 at 1.5 atm, 80 °C and 100% RH. Test protocols were developed to monitor the performance losses and characterize them in terms of activity for the oxygen reduction reaction (ORR), oxygen transport in the electrode and proton transport in the membrane and cathode catalyst layer. Despite the nearly double initial ORR activity, the PtCo/C electrode degraded faster due to the leaching of Co from the catalyst that had started even before the imposition of the AST potential cycles. Commensurate with Co leaching, Co poisoning of ionomer is responsible for the inferior performance of d-PtCo/C electrode at high current densities both before and after AST.